Pusa Pickling Cucumber-8: An early high yielding gynoecious parthenocarpic variety for protected cultivation and export - Munshi, A D; Sureja, Amish K; Behera, T K; Tomar, B S; Singh, J; S S Dey (Indian Horticulture, 2026)
Pusa Pickling Cucumber-8 is an extra-early, high-yielding gynoecious parthenocarpic variety developed by ICAR-IARI, New Delhi for protected cultivation in North Indian plains. It is specifically suited for off-season (winter) production under low-cost polyhouse conditions, overcoming temperature limitations of open-field cultivation. The variety produces market-preferred fruits without pollination, ensuring consistent yield and quality. Fruits are uniform, dark green, glossy, cylindrical, and possess tender skin with crispy flesh, ideal for pickling and export. It records an average yield of 84.81 t/ha, which is 19.60% higher than the commercial hybrid Annaxo. With early maturity (40–45 days), high productivity, and superior fruit quality, this variety offers a cost-effective alternative to expensive hybrids for farmers and export-oriented production systems.